Bilateral Acromioclavicular Septic Arthritis as an Initial Presentation of Streptococcus pneumoniae Endocarditis. (1st June 2014) - Hashemi-Sadraei, Neda; Gupta, Rohan; Machicado, Jorge D.; Govindu, Rukma
Abstract : Infective endocarditis (IE) is infrequently associated with septic arthritis. Moreover, septic arthritis of the acromioclavicular (AC) joint is rarely reported in the literature. We report a case of Streptococcus pneumoniae IE in a patient who presented with bilateral AC joint septic arthritis and we review the literature on the topic.